Manual backchannel responses in signers' conversations in Swedish Sign Language. (September 2016) - Mesch, Johanna
Abstract: The current study aims to determine the manual backchannel responses that signers use in Swedish Sign Language discourse by analyzing a subset of the SSL Corpus. The investigation found 20% of the backchannel responses in this data to be manual. The study focuses on the manual backchannel responses that consist of signs (mostly the sign gloss YES) and gesture-like signs (PU "palms up"), and other manual activities, which can occur at a relatively low height in signing space. With respect to age groups, younger signers engage in more weak manual activity than older signers. Highlights: Manual backchannel responses consist of signs, gesture-like signs and other manual activities. Manual backchannel responses occur mostly at a relatively low height in signing space. Younger signers engage in more weak manual activity than older signers in term of the backchanneling function.